Polymer composite material and new energy automobile wire duct
By adding ultrafine powder carboxy-butadiene butadiene rubber, epoxy POSS and other components to polyvinyl chloride plastics, a highly crosslinked three-dimensional network structure and adding flexible chain segments, the brittleness and impact strength of polyvinyl chloride plastics at low temperatures is solved. The problem of insufficient has significantly improved the thermal stability and mechanical properties of polymer composites.
Patent Information
- Application Number
- CN202411281643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-07
AI Technical Summary
PVC plastics exhibit brittleness at low temperatures and have low impact strength, which limits their application scenarios.
Using polymer composite materials, the composition includes PVC resin, ultrafine powder carboxylic styrene butadiene rubber, epoxy POSS, curing agent, carbon black, composite stabilizer and plasticizer, and the formation of a highly crosslinked three-dimensional network structure and increase flexibility chain segments to improve the thermal stability and mechanical properties of the material.
It improves the thermal stability and mechanical properties of polymer composites, enhances impact resistance, and maintains good impact resistance especially at low temperatures.
Smart Images

Figure CN119391101A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer composite materials, in particular to a polymer composite material and a new energy vehicle wiring duct. Background Art
[0002] Polyvinyl chloride plastic is made by the polymerization of vinyl chloride monomer and is one of the commonly used thermoplastic plastics. It has the advantages of flame retardancy, insulation, oil resistance, acid and alkali resistance, and excellent electrical properties. It has a wide range of uses and low prices, and plays an important role in the national economy.
[0003] However, polyvinyl chloride plastic also has many disadvantages, such as low impact strength and brittleness at low temperatures, which to a certain extent limits its application scenarios. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a polymer composite material and a new energy vehicle wiring duct.
[0005] The technical solutions adopted are as follows:
[0006] A polymer composite material, comprising the following components in parts by weight:
[0007] 80-100 parts of PVC resin, 15-30 parts of ultrafine powder carboxyl styrene butadiene rubber, 5-15 parts of epoxy POSS, 4-12 parts of curing agent, 10-40 parts of carbon black, 1-5 parts of composite stabilizer, and 5-10 parts of plasticizer.
[0008] Further, the preparation method of the epoxy POSS is as follows:
[0009] After isopropanol and tetramethylammonium hydroxide aqueous solution are mixed, the isopropanol solution of 3-glycidyl propoxymethoxysilane is added dropwise under stirring. After the addition is completed, the reaction is stirred for 5-10 hours, and the isopropanol is distilled off under reduced pressure. Toluene is added and the temperature is raised to reflux for 5-10 hours. After the reaction is completed, the room temperature is restored, the reaction solution is washed with saturated sodium chloride solution, and the toluene is finally distilled off under reduced pressure.
[0010] Furthermore, the mass concentration of the tetramethylammonium hydroxide aqueous solution is 1%-10%.
[0011] Furthermore, the curing agent is a long carbon chain aliphatic polyamine.
[0012] Furthermore, the long carbon chain aliphatic polyamine is a diaminoalkane with ≥10 carbon atoms.
[0013] Furthermore, the long carbon chain aliphatic polyamine is diaminododecane.
[0014] Furthermore, the composite stabilizer includes lanthanum acetylacetonate, zinc stearate, hydrotalcite and antioxidant 1010.
[0015] Furthermore, the mass ratio of the lanthanum acetylacetonate, zinc stearate, hydrotalcite and antioxidant 1010 is 3-6:3-6:1-2:0.1-1.
[0016] Furthermore, the plasticizer is any one or more combinations of dimethyl phthalate, diethyl phthalate, di-n-butyl phthalate, dioctyl phthalate, butyl benzyl phthalate, di(2-ethyl)hexyl phthalate, and diisononyl phthalate.
[0017] The present invention also provides a new energy vehicle wiring duct, which is prepared from the above-mentioned polymer composite material.
[0018] Beneficial effects of the present invention:
[0019] The invention provides a polymer composite material. POSS is a kind of organosilicon compound with a special molecular structure. The molecule of the POSS is based on an inorganic silicon oxygen skeleton as the core and is surrounded by organic groups on the periphery. The inorganic core provides the material with good heat resistance, and the peripheral organic groups can enhance the compatibility with PVC resin. Therefore, the POSS is a good modifier for preparing PVC-based polymer composite materials. In the invention, a long carbon chain aliphatic polyamine is selected as a curing agent of epoxy POSS to form a highly cross-linked three-dimensional network structure. The cross-linked structure forms a semi-interpenetrating network with a PVC matrix, effectively restricts the movement of small molecular segments in the cured product, and improves the thermal stability and mechanical properties of the polymer composite material. Moreover, the flexible segments contained in the POSS can greatly improve the toughness of the polymer composite material and improve the impact resistance.
[0020] During the blending process, the ultrafine powder carboxyl styrene butadiene rubber can directly serve as the stress concentration center to generate cracks or shear bands. When cracks or shear bands occur and grow, they will absorb a lot of energy, thereby improving the toughness of the polymer composite material and improving the impact resistance. The carboxyl group contained in it can not only play a role in increasing the volume as an active group, but also react with amino and epoxy groups to increase the degree of internal crosslinking and improve mechanical properties. The composite stabilizer can not only coordinate with the active chlorine atoms in the PVC molecules to make the C-Cl bond tend to be stable and not easy to break, thereby playing a stabilizing role, but also can significantly reduce the temperature of the combustion system together with the epoxy POSS, dilute the combustible gas, and isolate oxygen, thereby achieving a flame retardant effect;
[0021] The polymer composite material prepared by the invention has relatively excellent mechanical properties and can also maintain certain impact resistance at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The fracture morphology of the polymer composite material prepared in Example 1 under a 2000x electron microscope is shown. A large number of plastic fibers can be seen. Compared with pure PVC material that is prone to brittle fracture, the toughness is improved and the impact resistance is enhanced.
[0023] Figure 2 This is the fracture morphology of the polymer composite material prepared in Comparative Example 5 under a 2000x electron microscope. Compared with the polymer composite material prepared in Example 1, the plastic fibers at the fracture are greatly reduced, which shows that the addition of 1,12-diaminododecane with a long carbon chain plays a positive role in improving the toughness of the polymer composite material. DETAILED DESCRIPTION
[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0025] PVC resin: S-1000, Sinopec;
[0026] Ultrafine powder carboxyl styrene butadiene rubber: NarpowVP201, Beijing Beihuayan Chemical New Technology Company;
[0027] Epoxy POSS: homemade;
[0028] 1,12-Diaminododecane: Nantong Runfeng Petrochemical Co., Ltd.;
[0029] Carbon black: Shandong Kasong New Materials Co., Ltd.;
[0030] Lanthanum acetylacetonate: Shandong Senya New Materials Co., Ltd.;
[0031] Zinc stearate: Shandong Kasong New Materials Co., Ltd.;
[0032] Hydrotalcite: Jiangsu Bosite Chemical Technology Co., Ltd.;
[0033] Antioxidant 1010: Dongguan Baoxu Chemical Technology Co., Ltd.
[0034] Plasticizer DOP: Dongguan Baoxu Chemical Technology Co., Ltd.
[0035] Embodiment 1:
[0036] This embodiment provides a polymer composite material, which comprises the following components in parts by weight:
[0037] 95 parts of PVC resin, 25 parts of ultrafine powder carboxyl styrene-butadiene rubber, 15 parts of epoxy POSS, 10 parts of 1,12-diaminododecane, 30 parts of carbon black, 2 parts of lanthanum acetylacetonate, 2 parts of zinc stearate, 0.5 parts of hydrotalcite, 0.25 parts of antioxidant 1010, and 6 parts of plasticizer DOP.
[0038] Wherein, the preparation method of epoxy POSS is as follows:
[0039] In a three-necked flask equipped with a stirring device, a dropping funnel and a thermometer, 500 ml of isopropanol and 25 g of a 5% tetramethylammonium hydroxide aqueous solution were added and mixed; 200 g of 3-glycidyl propoxy trimethoxy silane was mixed with 100 ml of isopropanol and placed in a dropping funnel; the mixture was added dropwise to the three-necked flask at a uniform rate under stirring and the addition was completed within 1 hour; after the addition was completed, the reaction was continued to stir at room temperature for 6 hours; the isopropanol was removed by vacuum distillation; 500 ml of toluene was added to dissolve the intermediate product; the temperature was raised to reflux for reaction for 6 hours; after the reaction was completed, the room temperature was restored; the reaction solution was washed with a saturated sodium chloride solution until the pH value of the washed reaction solution was 7; the reaction solution was dried over anhydrous sodium sulfate overnight; and the toluene was removed by vacuum distillation to obtain a colorless, transparent, viscous liquid, i.e., epoxy POSS.
[0040] The preparation method of the above polymer composite material is as follows:
[0041] PVC resin, ultrafine powder carboxyl styrene-butadiene rubber, epoxy POSS, 1,12-diaminododecane, carbon black, lanthanum acetylacetonate, zinc stearate, hydrotalcite, antioxidant 1010 and plasticizer DOP are mixed, melt-blended and extruded into granules through a twin-screw extruder. The temperatures of each section of the extruder are: 180°C (die head), 185°C, 180°C, 175°C, 170°C, 165°C. The obtained granules are dried and placed in a mold, and hot-pressed in a flat vulcanizer. The hot-pressing temperature is 170°C and the molding time is 5 minutes. After molding, the granules are kept at 80°C for 5 minutes for demolding.
[0042] Embodiment 2:
[0043] This embodiment provides a polymer composite material, which comprises the following components in parts by weight:
[0044] 100 parts of PVC resin, 30 parts of ultrafine powder carboxyl styrene-butadiene rubber, 15 parts of epoxy POSS, 12 parts of 1,12-diaminododecane, 40 parts of carbon black, 2 parts of lanthanum acetylacetonate, 2 parts of zinc stearate, 0.5 parts of hydrotalcite, 0.25 parts of antioxidant 1010, and 5 parts of plasticizer DOP.
[0045] Wherein, the preparation method of epoxy POSS is the same as that of Example 1;
[0046] The preparation method of the above polymer composite material is as follows:
[0047] PVC resin, ultrafine powder carboxyl styrene-butadiene rubber, epoxy POSS, 1,12-diaminododecane, carbon black, lanthanum acetylacetonate, zinc stearate, hydrotalcite, antioxidant 1010 and plasticizer DOP are mixed, melt-blended and extruded into granules through a twin-screw extruder. The temperatures of each section of the extruder are: 180°C (die head), 185°C, 180°C, 175°C, 170°C, 165°C. The obtained granules are dried and placed in a mold, and hot-pressed in a flat vulcanizer. The hot-pressing temperature is 170°C and the molding time is 5 minutes. After molding, the granules are kept at 80°C for 5 minutes for demolding.
[0048] Embodiment 3:
[0049] This embodiment provides a polymer composite material, which comprises the following components in parts by weight:
[0050] 80 parts of PVC resin, 15 parts of ultrafine powder carboxyl styrene-butadiene rubber, 10 parts of epoxy POSS, 8 parts of 1,12-diaminododecane, 20 parts of carbon black, 2 parts of lanthanum acetylacetonate, 2 parts of zinc stearate, 0.5 parts of hydrotalcite, 0.25 parts of antioxidant 1010, and 5 parts of plasticizer DOP.
[0051] Wherein, the preparation method of epoxy POSS is the same as that of Example 1;
[0052] The preparation method of the above polymer composite material is as follows:
[0053] PVC resin, ultrafine powder carboxyl styrene-butadiene rubber, epoxy POSS, 1,12-diaminododecane, carbon black, lanthanum acetylacetonate, zinc stearate, hydrotalcite, antioxidant 1010 and plasticizer DOP are mixed, melt-blended and extruded into granules through a twin-screw extruder. The temperatures of each section of the extruder are: 180°C (die head), 185°C, 180°C, 175°C, 170°C, 165°C. The obtained granules are dried and placed in a mold, and hot-pressed in a flat vulcanizer. The hot-pressing temperature is 170°C and the molding time is 5 minutes. After molding, the granules are kept at 80°C for 5 minutes for demolding.
[0054] Embodiment 4:
[0055] This embodiment provides a polymer composite material, which comprises the following components in parts by weight:
[0056] 100 parts of PVC resin, 20 parts of ultrafine powder carboxyl styrene-butadiene rubber, 15 parts of epoxy POSS, 6 parts of 1,12-diaminododecane, 30 parts of carbon black, 2 parts of lanthanum acetylacetonate, 2 parts of zinc stearate, 0.5 parts of hydrotalcite, 0.25 parts of antioxidant 1010, and 5 parts of plasticizer DOP.
[0057] Wherein, the preparation method of epoxy POSS is the same as that of Example 1;
[0058] The preparation method of the above polymer composite material is as follows:
[0059] PVC resin, ultrafine powder carboxyl styrene-butadiene rubber, epoxy POSS, 1,12-diaminododecane, carbon black, lanthanum acetylacetonate, zinc stearate, hydrotalcite, antioxidant 1010 and plasticizer DOP are mixed, melt-blended and extruded into granules through a twin-screw extruder. The temperatures of each section of the extruder are: 180°C (die head), 185°C, 180°C, 175°C, 170°C, 165°C. The obtained granules are dried and placed in a mold, and hot-pressed in a flat vulcanizer. The hot-pressing temperature is 170°C and the molding time is 5 minutes. After molding, the granules are kept at 80°C for 5 minutes for demolding.
[0060] Embodiment 5:
[0061] This embodiment provides a polymer composite material, which comprises the following components in parts by weight:
[0062] 80 parts of PVC resin, 30 parts of ultrafine powder carboxyl styrene butadiene rubber, 10 parts of epoxy POSS, 4 parts of 1,12-diaminododecane, 20 parts of carbon black, 2 parts of lanthanum acetylacetonate, 2 parts of zinc stearate, 0.5 parts of hydrotalcite, 0.25 parts of antioxidant 1010, and 8 parts of plasticizer DOP.
[0063] Wherein, the preparation method of epoxy POSS is the same as that of Example 1;
[0064] The preparation method of the above polymer composite material is as follows:
[0065] PVC resin, ultrafine powder carboxyl styrene-butadiene rubber, epoxy POSS, 1,12-diaminododecane, carbon black, lanthanum acetylacetonate, zinc stearate, hydrotalcite, antioxidant 1010 and plasticizer DOP are mixed, melt-blended and extruded into granules through a twin-screw extruder. The temperatures of each section of the extruder are: 180°C (die head), 185°C, 180°C, 175°C, 170°C, 165°C. The obtained granules are dried and placed in a mold, and hot-pressed in a flat vulcanizer. The hot-pressing temperature is 170°C and the molding time is 5 minutes. After molding, the granules are kept at 80°C for 5 minutes for demolding.
[0066] Comparative Example 1:
[0067] The method is substantially the same as Example 1, except that the ultrafine powder carboxyl styrene butadiene rubber is not added.
[0068] Comparative Example 2:
[0069] The method is substantially the same as Example 1, except that superfine powdered styrene butadiene rubber is used instead of superfine powdered carboxylated styrene butadiene rubber.
[0070] Comparative Example 3:
[0071] The method is substantially the same as Example 1, except that epoxy resin is used instead of epoxy-based POSS.
[0072] Comparative Example 4:
[0073] The method is substantially the same as Example 1, except that epoxy POSS is not added.
[0074] Comparative Example 5:
[0075] The process is substantially the same as Example 1, except that ethylenediamine is used instead of 1,12-diaminododecane.
[0076] Performance Test:
[0077] The polymer composite materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were made into samples for performance testing;
[0078] The tensile properties are tested according to GB / T 1040-2006 "Test method for tensile properties of plastics", the specimen is dumbbell-shaped, and the tensile speed is 50mm / min;
[0079] The notched impact strength is tested according to GB / T 1843-1996 "Plastic Izod Beam Impact Test Method", with a V-shaped notch, a sample size of 80mm×10mm×4mm, and a notch depth of 2mm;
[0080] Low temperature impact strength test: Place the sample in a liquid nitrogen environment at -40°C for 30 minutes and then repeat the above notched impact strength test;
[0081] The test results are shown in Table 1 below:
[0082] Table 1:
[0083]
[0084] It can be seen from Table 1 above that the polymer composite material prepared by the present invention has relatively excellent mechanical properties and can also maintain a certain impact resistance at low temperatures.
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polymer composite material, characterized in that: In parts by weight, it comprises the following components: 80-100 parts of PVC resin, 15-30 parts of ultrafine powder carboxyl styrene butadiene rubber, 5-15 parts of epoxy POSS, 4-12 parts of curing agent, 10-40 parts of carbon black, 1-5 parts of composite stabilizer, and 5-10 parts of plasticizer.
2. The polymer composite material according to claim 1, characterized in that: The preparation method of the epoxy POSS is as follows: After isopropanol and tetramethylammonium hydroxide aqueous solution are mixed, the isopropanol solution of 3-glycidyl propoxymethoxysilane is added dropwise under stirring. After the addition is completed, the reaction is stirred for 5-10 hours, and the isopropanol is distilled off under reduced pressure. Toluene is added and the temperature is raised to reflux for 5-10 hours. After the reaction is completed, the room temperature is restored, the reaction solution is washed with saturated sodium chloride solution, and the toluene is finally distilled off under reduced pressure.
3. The polymer composite material according to claim 2, characterized in that: The mass concentration of the tetramethylammonium hydroxide aqueous solution is 1%-10%.
4. The polymer composite material according to claim 1, characterized in that: The curing agent is a long carbon chain aliphatic polyamine.
5. The polymer composite material according to claim 4, characterized in that: The long carbon chain aliphatic polyamine is a diaminoalkane with ≥10 carbon atoms.
6. The polymer composite material according to claim 5, characterized in that: The long carbon chain aliphatic polyamine is diaminododecane.
7. The polymer composite material according to claim 1, characterized in that: The composite stabilizer includes lanthanum acetylacetonate, zinc stearate, hydrotalcite and antioxidant 1010.
8. The polymer composite material according to claim 7, characterized in that: The mass ratio of the lanthanum acetylacetonate, zinc stearate, hydrotalcite and antioxidant 1010 is 3-6:3-6:1-2:0.1-1.
9. The polymer composite material according to claim 1, characterized in that: The plasticizer is any one or more combinations of dimethyl phthalate, diethyl phthalate, di-n-butyl phthalate, dioctyl phthalate, butyl benzyl phthalate, di(2-ethyl)hexyl phthalate, and diisononyl phthalate.
10. A new energy vehicle cable duct, characterized in that: The polymer composite material is prepared from any one of claims 1 to 9.